Pengelompokan Data Wilayah Rawan Bencana Alam di Pulau Jawa - Maulana Ichsan; Erlangga Alfath Wijaya; Mohammad Raffi Mahendra; Faisal Amar Alfarouk (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Java Island is the most disaster-prone region in Indonesia because Java Island is located in a convex zone (meeting each other) between two tectonic plates, namely the Eurasian Plate in the north, and the Indo-Australian Plate which causes the formation of volcanoes and earthquakes. Java Island which is near the convergence zone of these plates causes Java to become a disaster-prone zone, with many volcanoes that often erupt and experience many earthquakes. Volcanoes are formed due to the movement of hot magma from the meeting of plates to the earth's surface. While earthquakes occur due to the instantaneous movement of earth plates.